Design and Implementation of SkillShare Campus: A Web-Based Collaborative Learning Platform for Higher Education - Choirul Anam; Ismila Alya Iqlima; Maylyan Restu Sudifta; Irmansyah Hafiz Samir; M Adamu Islam Mashuri (Universitas Negeri Surabaya, 2025)
The rapid development of information technology has transformed higher education learning toward more flexible and collaborative models. This study aims to design and implement SkillShare Campus, a web-based collaborative learning platform that facilitates skill sharing and class management between students and tutors. The system was developed through needs analysis, system design, implementation, and functional testing using the black box method. SkillShare Campus was implemented using PHP and MySQL and provides features such as user authentication, skill management, and class creation. Functional testing results indicate that all core features operate according to user requirements. Therefore, SkillShare Campus effectively supports collaborative and self-directed learning in higher education environments.